2013
DOI: 10.1002/eji.201243217
|View full text |Cite
|
Sign up to set email alerts
|

IRAK4 turns IL‐10+ phospho‐FOXO+ monocytes into pro‐inflammatory cells by suppression of protein kinase B

Abstract: IRAK4, a serine/threonine kinase is a central adaptor protein in TLR signaling. To better understand the clinical significance of IRAK4 deficiency we examined the impact of IRAK4 on bacterial recognition in human monocytes. We show that IRAK4 knockdown modulates monocyte-derived cytokine secretion in response to Staphylococcus aureus and Streptococcus pneumoniae, resulting in decreased IL-12 and elevated IL-10 production, a finding also reproducible with ligands for TLR2 and TLR4. In contrast, silencing of MyD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
3
16
1
Order By: Relevance
“…3). Thus, similarly to our previous study, our data identify IL-10 as an important mediator of tolerance (26). It has further been suggested that increased TNF levels in monocytes and macrophages after rapamycin treatment reflect loss of IL-10 (32, 34).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…3). Thus, similarly to our previous study, our data identify IL-10 as an important mediator of tolerance (26). It has further been suggested that increased TNF levels in monocytes and macrophages after rapamycin treatment reflect loss of IL-10 (32, 34).…”
Section: Discussionsupporting
confidence: 90%
“…IL-10 production, which suppresses IL-12 expression and the T cell response to alloantigen (26). This tolerogenic response is mediated in a PI3K/PKB/Akt/mTOR-dependent pathway and counterregulated by IRAK4 (26). Similarly, in the study described in reference 29), the PI3K/Akt pathway reciprocally regulated P. gingivalis LPS-induced IL-10 and IL-12 synthesis, notably, in a TLR2-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations